Vaikuntha Vishnu - Temples of India Project Team (Jio Institute, 2024)
This important image of Vaikuntha Vishnu reveals the presence of the Pancharatra form of Vaishnavism at Harsha Hill. Pancharatra had spread to various regions of Rajasthan from the eighth century CE onwards, with its most visible manifestations in temples like the Harshatmata Temple of Abhaneri. This image reveals its spread, even if in a limited manner, to the region of Shekhavati. The niches on either side depict damsels and musicians. The four faces of Vaikuntha Vishnu represent its four emanations/vyuha- Vasudeva, Sankarshana, Pradyumna and Aniruddha. The side faces are that of boar and lion, typical of Vaikuntha iconography. He is seated in the lalitasana pose.